Proceedings of the First International Conference on Materials Engineering and Management - Engineering Section (ICMEMe 2018) 2019
DOI: 10.2991/icmeme-18.2019.7
|View full text |Cite
|
Sign up to set email alerts
|

Potency of Sugarcane Bagasse Ash Partial Subtitution of Cement in Concrete

Abstract: the availability of sugarcane bagasse ash produced by Arasoe Sugar Factory, it is not used utilized. That sugarcane bagasse ash has size very fine that it can pollute the air. The sugarcane bagasse ash has silicate content, and it has pozzolan properties. The needs of construction material are something that to think about that. It is an alternative to substitute the using of cement in concrete construction. This study is aimed to find the potential of sugarcane bagasse ash in Arasoe Sugar Factory for partial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Between 5% and 20% sugarcane bagasse ash replacement, an acceptable strength of concrete can be obtained [41,42]. Other studies have shown that sugarcane bagasse is a good replacement material for concrete production [43,44]. Also, 5 to 15% sugarcane bagasse ash increased the compressive strength and workability of concrete [45][46][47], while other authors have recorded compressive strength produced from sugarcane bagasse ash that was higher than cement concrete alone at 5% replacement or more [48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Between 5% and 20% sugarcane bagasse ash replacement, an acceptable strength of concrete can be obtained [41,42]. Other studies have shown that sugarcane bagasse is a good replacement material for concrete production [43,44]. Also, 5 to 15% sugarcane bagasse ash increased the compressive strength and workability of concrete [45][46][47], while other authors have recorded compressive strength produced from sugarcane bagasse ash that was higher than cement concrete alone at 5% replacement or more [48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%